STUDI TENTANG BUDIDAYA TANAMAN KENTANG Solzum Tuberosum L DI DATARAN TINGGI DIENG KAJIAN DARI ASPEK EKONOMI DAN LINGKUNGAN (A STUDY IN ECONOMICAL AND ENVIRONEMENTAL ASPECTS TO THE CULTIVATION OF POTATOES Solzum Tuberosum L IN DIENG PLATEU) - , Bondansari; Sularso, Kusmantoro Edy; Dewanto, Eko (Pembangunan Pedesaan, 2011)
Dieng Plateau is a region that is suitable for the development potatoes (Solanum tuberosum L.). Potato farming system is implemented on the sloping land, but conservation technologies are insufficient, so the productivity has decreased. Seemingly, the farming management also causes environmental disturbances, such as erosion, and excessive use of pesticides impact. This research aims were identifying the use of farm inputs used to anticipate the decrease of soybean productivities, and assessing the sustainability of potato farming from the economic aspect into account environmental factors. The research was conducted using a descriptive analytical method with a simple cluster sampling. Data were collected from the farm inputs and supporting data such as, product prices and saprodi, receipts and related information with potato farming activities. The results showed that used of seed, labor and inorganic fertilizer in the planting season in 2008 was more than the planting season in 2009. Used of organic fertilizers in the planting season in 2009 was more than the season planting in 2008. Potato productivity in the planting season in 2008 was higher than that in the planting season in 2009. Monoculture cropping pattern with very intensive in the use of pesticides, cropping system in the direction of the slope and bench terraces that have not been introduced well often caused environmental problems, such as landslides, floods with mud, erosion and declining productivity of potato. Potato farming was still profitable in financial terms but economically (socially), it was not feasible to be commercialized.